Progesterone exerts antidepressant-like effect in a mouse model of maternal separation stress through mitigation of neuroinflammatory response and oxidative stress - Ali Nouri; Farzaneh Hashemzadeh; Amin Soltani; Elham Saghaei; Hossein Amini-Khoei (Taylor & Francis Group, 2020)
Context Experiencing early-life adversity plays a key role in the development of mood disorders in adulthood. Experiencing adversities during early life period negatively affects brain development. Sex steroids such as progesterone affect the brain structure and functions and subsequently affects behaviour. Objective We assess the antidepressant-like effect of progesterone in a mouse model of maternal separation (MS) stress, focussing on its anti-neuroinflammatory and antioxidative effects. Materials and methods NMRI mice were treated with progesterone (10, 50, and 100 mg/kg, i.p., respectively) for 14 days. Valid behavioural tests including forced swimming test (FST), splash test and open field test (OFT) were used. Quantitative reverse transcription-PCR (qRT-PCR) was used for evaluation of genetic expression in the hippocampus. Antioxidant capacity was assessed by the FRAP method and the level of malondialdehide by TBA. Results MS provoked depressive-like behaviour in mice. Treatment of MS mice with progesterone increased the grooming activity time in the splash test and decreased the immobility time in the FST. In addition, progesterone decreased the expression of inflammatory genes related to neuroinflammation (IL-1β, TNF-α, TLR4 and NLRP3) as well as increased the antioxidant capacity and decreased the lipid peroxidation (MDA) in the hippocampus. Discussion and Conclusion Administration of progesterone significantly mitigated the negative effects of MS on behaviours relevant to depressive-like behaviour as well as attenuated neuro-immune response and oxidative stress in the hippocampus of MS mice. In this context, we conclude that progesterone, at least partially, via attenuation of oxidative stress and neuroinflammation, exerts antidepressant-like effects.